Anti-oxidant and Anti-inflammatory Properties of Stem and Root Extracts of Cissus quadrangularis (Veldt Grape) - Kumar, Dinesh; Guna, R.; Abbirami, E.; Gayathri, N.; Karthik, R.; Sivasudha, T. (Asian Journal of Engineering and Applied Technology, 2019)
Free radicals are unstable, highly reactive molecules, creates oxidative stress in our body by attacking healthy cells and tissue biomolecules. They are usually neutralized by the antioxidant mechanisms in our system. When the antioxidant mechanism fails to stabilize the radicals, we need external antioxidants to protect our cells from oxidative damage. The objective of present study is to evaluate the antioxidant and anti-inflammatory properties of stem and root extracts of the plant Cissus quadrangularis. Stem and root powders of CQ was extracted with different solvent and they were tested against the synthetic free radical DPPH, ABTS, NO, H2O2 and FRAP with the reference standard BHT. The in vitro anti-inflammatory activity assay was also performed for all the extracts along with the reference standard naproxen. The 50 percentage of inhibitory concentration (IC50-μg/ml of extract) values of ethanol fraction from both stem and root extract was found to be in DPPH- (IC50: 32±0.07 & 28±0.02), ABTS- (IC50: 115±0.22 & 120±0.06), NO- (IC50: 13±0.05 & 47±0.13), H2O2- (IC50: 21±0.08 & 28±0.09), TAA- (PI: 73±0.16 & 66±0.22) and the protein denaturation assay showed the ethanol fraction has protective activity levels of 220±0.03 & 277±0.22 in stem and root extracts respectively. Results obtained from this study suggested that both stem and root extracts of CQ possesses potential antioxidant and anti-inflammatory properties.